In vitro rhizobia response and symbiosis process under aluminum stress - Ramirez, Maria D. Artigas; Silva, Jessica D. [UNESP]; Ohkama-Ohtsu, Naoko; Yokoyama, Tadashi (Canadian Science Publishing, Nrc Research Press, 2018)
Aluminum (Al) toxicity is a major problem affecting soil fertility, microbial diversity, and nutrient uptake of plants. Rhizobia response and legume interaction under Al conditions are still unknown; it is important to understand how to develop and improve legume cultivation under Al stress. In this study, rhizobia response was recorded under different Al concentrations. Al effect on rhizobial cells was characterized by combination with different two pH conditions. Symbiosis process was compared between alpha- and beta-rhizobia inoculated onto soybean varieties. Rhizobial cell numbers was decreased as Al concentration increased. However, induced Al tolerance considerably depended on rhizobia types and their origins. Accordingly, organic acid results were in correlation with growth rate and cell density which suggested that citric acid might be a positive selective force for Al tolerance and plant interaction on rhizobia. Al toxicity delayed and interrupted the plant-rhizobia interaction and the effect was more pronounced under acidic conditions. Burkholderia fungorum VTr35 significantly improved plant growth under acid-Al stress in combination with all soybean varieties. Moreover, plant genotype was an important factor to establish an effective nodulation and nitrogen fixation under Al stress. Additionally, tolerant rhizobia could be applied as an inoculant on stressful agroecosystems. Furthermore, metabolic pathways have still been unknown under Al stress.
Keywords: aluminum stress; Bradyrhizobium; Burkholderia; citric acid; Glycine max